2006
DOI: 10.1038/nature05097
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin/NFAT signalling regulates pancreatic β-cell growth and function

Abstract: The growth and function of organs such as pancreatic islets adapt to meet physiological challenges and maintain metabolic balance, but the mechanisms controlling these facultative responses are unclear. Diabetes in patients treated with calcineurin inhibitors such as cyclosporin A indicates that calcineurin/nuclear factor of activated T-cells (NFAT) signalling might control adaptive islet responses, but the roles of this pathway in beta-cells in vivo are not understood. Here we show that mice with a beta-cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
405
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 410 publications
(437 citation statements)
references
References 29 publications
18
405
2
5
Order By: Relevance
“…In vitro, reactive oxygen species were shown to inhibit the activity of the calcium/calmodulin-dependent serine/threonine phosphatase calcineurin [35], while recent data demonstrate the pivotal role of calcineurin for beta cell proliferation and human insulin gene transcription [8,9,36]. However, IL-1β did not change calcineurin phosphatase activity in HIT cells (data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…In vitro, reactive oxygen species were shown to inhibit the activity of the calcium/calmodulin-dependent serine/threonine phosphatase calcineurin [35], while recent data demonstrate the pivotal role of calcineurin for beta cell proliferation and human insulin gene transcription [8,9,36]. However, IL-1β did not change calcineurin phosphatase activity in HIT cells (data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…It has been shown by others that several Cn isoforms are expressed in osteoblasts (14). However, it has been demonstrated that whereas there is redundancy and compensation in response to the inhibition of different CnA catalytic subunits (29), the deletion of the Cnb1 regulatory subunit is sufficient to eliminate all Cn activity in several biological systems (19,30,31). Our results are consistent with these reports and demonstrate that Cnb1 deletion in osteoblasts is not compensated by any of the other Cn isoforms that were reported to be expressed in osteoblasts (Cn A␣, A␤, A␥, and B2).…”
Section: Discussionmentioning
confidence: 99%
“…However, because of its well-known diabetogenic effect, its utility is sometimes limited. The suggested mechanisms for the development of CsA-induced diabetes are the following: decreased calcineurin/nuclear factor of activated T-cells-dependent insulin gene transcription, [15][16][17] impairment of priming of the insulin secretory granule, 17,18 decreased b-cell mass 19 and dysfunction of hepatocyte nuclear factor-4a. 20 Although the mechanism by which CsA mediates diabetes is still unclear, CsA ultimately interferes with insulin secretion in b-cells, 21,22 which might contribute to the development of PTDM.…”
Section: Introductionmentioning
confidence: 99%